One pot glucose detection by [Fe-III(biuret-amide)] immobilized on mesoporous silica nanoparticles: an efficient HRP mimic - Malvi, Bharmana; Panda, Chakadola; Dhar, Basab B.; Sen Gupta, Sayam (Chemical Communications, 2012)
An [Fe-III(biuret-amide)] complex has been immobilized onto mesoporous silica nanoparticles via Cu(I) catalyzed azide-alkyne click chemistry. This hybrid material functions as an efficient peroxidase mimic and was successfully used for the quantitative determination of hydrogen peroxide and glucose via a one-pot colorimetric assay.